Adhesive Process of the Abdominal Cavity as a Risk Factor for the Development of Postoperative Intestinal Fistula - N. I. Ayushinova; E. E. Chepurnykh; I. A. Shurygina; E. G. Grigoriev (Acta Biomedica Scientifica, 2019)
Adhesive disease of the abdominal cavity remains one of the unresolved problems of abdominal surgery. The clinical picture of the pathological process is diverse, treatment of patients is not always effective, and decision-making on the use of certain medical methods is often difficult.The aim of the research was to assess the severity of the adhesive process and the likelihood of complications in patients with adhesive disease of the abdominal cavity.Materials and methods. We performed the retrospective analysis of 160 case histories of patients for the period 2006-2010, who, according to emergency indications, were admitted to the surgical department of the Irkutsk Regional Clinical Hospital with a clinic of acute adhesive intestinal obstruction against the background of adhesive disease. To assess the severity of the adhesive process, our own scale for assessing the adhesive process of the abdominal cavity was developed and tested in clinical conditions. To assess the likelihood of developing postoperative unformed intestinal fistulas, a prospective analysis of the treatment of 36 patients with acute adhesive intestinal obstruction was performed.Results. The severity of the adhesive process in the operated patients was 13 (10-15) points, which indicates a pronounced adhesive process. In patients operated repeatedly for commissural intestinal obstruction, the severity of the adhesion process according to the proposed scale was 14 (14-15) points, which corresponds to pronounced adhesion of the abdominal organs. Based on the proposed scale, the probability of developing postoperative unformed intestinal fistulas was calculated. The sensitivity and accuracy of the probability scale was 71 % (CONSORT). Thus, an intraoperative assessment of the severity of the adhesive process allows us to predict the likelihood of postoperative external intestinal fistula.